Chemical Classification of Sediments in JVX -Well, Greater Ughelli Depobelt Niger Delta Basin, Nigeria - T.J. Fregene; N. Onyeachonam (Journal of Applied Sciences and Environmental Management, 2021)
This study evaluate the Chemical classification of sediments in JVX well, Greater Ughelli Depo belt Niger Delta Basin. Samples collected from different intervals were analyzed using geochemical proxies. Agbada Formation was suggested for the sampled intervals due to the presence of shaleand sand intercalations. lithofacies units gotten from sampled intervals are Sand, Shale and Shaly sand facies . The sands are milky in colour, translucent to opaque, medium to coarse grain, subangular to subrounded and are moderately sorted while the shales are Grey in colour, fissile with the presence of lignite streak and calcareous materials.The geochemical studies of the sediments revealed that SiO2 is the dominant oxide followed by Al2O3 and Fe2O3 which constitutes over 90% while others like CaO, K2O, TiO2, Na2O and MgO constitute 10%. The sediments were classified as Fe-shale, Fe-sand and Quartz arenite. Samples that plotted in the quartz arenites region suggests an intense degree of weathering and reworking. The SiO2/Al2O3 ratios for the sediments in the well are appreciably high indicating that the samples have been heavily weathered, evidenced from the enrichment of quartz and depletion of feldspars. Also, the relatively high concentrations of Fe2O3 and TiO2 is an indication of iron-titanium minerals such as haematite and anatase retiles.